ln(5x)+ln(2+x)=5

Simple and best practice solution for ln(5x)+ln(2+x)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(5x)+ln(2+x)=5 equation:


Simplifying
ln(5x) + ln(2 + x) = 5

Remove parenthesis around (5x)
ln * 5x + ln(2 + x) = 5

Reorder the terms for easier multiplication:
5ln * x + ln(2 + x) = 5

Multiply ln * x
5lnx + ln(2 + x) = 5
5lnx + (2 * ln + x * ln) = 5
5lnx + (2ln + lnx) = 5

Reorder the terms:
2ln + 5lnx + lnx = 5

Combine like terms: 5lnx + lnx = 6lnx
2ln + 6lnx = 5

Solving
2ln + 6lnx = 5

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-5 + 2ln + 6lnx = 5 + -5

Combine like terms: 5 + -5 = 0
-5 + 2ln + 6lnx = 0

The solution to this equation could not be determined.

See similar equations:

| 7y-4x=48 | | 7x+5y=41 | | 22.9-7y=5.4 | | (x-150)+(x)=1500 | | 1.1=4y+17.5 | | 22.9-7=5.4 | | 75=3(-6n-5)-n | | 9x^2+24x+17=0 | | -47x=-2162 | | A(n)=12+(n-1)(-5) | | -x+26=-2x-24 | | x-.3x=60 | | 3-1/X=0 | | 5.8n=26.1 | | X-(4x-7)=5x | | -12-2x=0 | | -79-22x=-20x+49 | | x^4+3x^3-x^2+8=0 | | y=logbx | | 3t-5=2t+2 | | 4x+32=x+11 | | 5h+14-2h=9-(2-3h) | | -x+43=3x+19 | | 10(x+2)+8x=18x+30 | | 11x-82=14x+86 | | 234=4.5r+4.5(r+30.8) | | (1/2x)(2x) | | -5g+3=8g+9 | | -310=2x+7(6x+6) | | 42-180= | | 2n-4=-18 | | 7x=17.92 |

Equations solver categories